EMPLOYEE PERFORMANCE IN PT BPD KALTIM KALTARA SAMARINDA - Nabila Nur Fajrina; Theresia Militina; Gusti Noorlitaria Achmad (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
In this study involving PT BPD Kaltim Kaltara Samarinda. In this study, to see the performance of employees used a sample of 162 respondents, based on the results of the questionnaire that has been distributed, it can be seen that the number of respondents to be analyzed was 162 respondents. The data analysis used by the author is the Structural Equation Model (SEM). Hypothesis testing is done by multivariate analysis carried out through the WarpPLS program. Data analysis through partial Least Square (PLS) is done through two stages, namely: First, Assessing the outer model or measurement model. Second, assess the inner model or structural model. The results showed that there was a positive and not significant effect between Openness on employee organizational citizenship behavior, There was a positive and significant effect between Conscientiousness on organizational citizenship behavior of employees, There was a positive and insignificant effect between Extraversion on organizational citizenship behavior of employees, There was an influence a positive and significant relationship between Agreeableness on organizational citizenship behavior of employees, There is a positive and significant influence between Neuroticism on organizational citizenship behavior of employees, There is a positive and insignificant effect between Openness on employee performance, There is a positive and insignificant effect between Conscientiousness on performance employees, There is a positive and significant influence between Extraversion on employee performance, There is a positive and significant effect between Agreeabl eness on employee performance, There is a positive and insignificant influence between Neuroticism on employee performance, There is a positive and not significant effect between organizational citizenship behavior on employee performance of PT BPD Kaltim Kaltara Samarinda Branch.